Simple Accounting as an Informal Governance Mechanism in Rural Community-Based Tourism Homestays - Admita; Yuni Deviyanti; Ria Aryani; Mita Purnamasari; Dini Murniaty (Jurnal Sains Terapan Pariwisata, 2026)
This study examines how simple accounting functions as an informal governance mechanism in community-based tourism homestay management. Using an interpretive qualitative approach, data were collected through semi-structured interviews, observation, and document analysis involving twelve homestay operators in Kalisoro Tourism Village, Central Java, Indonesia. The findings indicate that simple accounting practices improve recording discipline, support the separation of business and household finances, and generate reliable structured financial information for operational and strategic decision-making. Beyond technical functions, simple accounting enhances transparency, strengthens stakeholder accountability, and facilitates collective management within community-based tourism enterprises. By institutionalizing routine financial documentation, these practices contribute to operational control, planning capacity, and long-term business sustainability. The study demonstrates that context-adapted financial management practices function not merely as administrative tools but as governance mechanisms in rural tourism micro-enterprises. These findings highlight the role of simple accounting in strengthening governance and sustainability in tourism villages.